Soutenir le développement du pouvoir d’agir : une composante essentielle des soins spirituels au Québec - Cherblanc, Jacques (Studies in religion, 2020)
Since the early 1970s, spiritual care in the Quebec health care system has undergone deep transformations. These aim to adapt this service to the progressive secularization of the population and the health institutions themselves. In order to understand these transformations we conducted an inductive qualitative research (2011–2016) with 23 spiritual care professionals (SCP). Through semi-structured interviews, they shared “story-telling” of practices they considered specifically spiritual. The qualitative content analysis has revealed that their practices are distinct from other health professionals. Empowerment seems to be a key component of their practices. We present the different characteristics of this empowerment and suggest some ideas for the future of these stakeholders.